Ethnomedicine, Health Food and Nutraceuticals-Traditional Wisdom of Maternal and Child Health in India - Pushpangadan, Palpu; George, Varughese; Ijinu, Thadiyanparambil; Chithra, Manikantan Ambika (Edelweiss Applied Science and Technology, 2018)
Food and medicine are indispensable companions of humans since the very beginning of his existence. The early man explored his surroundings to locate materials of natural origin for food and medicine. He continued his search in the plant and animal kingdoms to expand his food basket, to heal his ailments and discomforts. The desire to attain vitality and longevity also prompted the early man to experiment with whatever available in his immediate neighbourhood. By a process of trial and error, observation and empirical reasoning and inference the early man made conscious selections of a variety of biological materials to enhance his health, to alleviate pain or to treat other physical and mental ailments. The knowledge thus gathered was passed on to succeeding generations. Creative members of the succeeding generations incrementally improved and even added new knowledge to this body of traditional knowledge system. This traditional wisdom has come down to us from our ancestors and we now term it as traditional knowledge or ethnic knowledge. We find this knowledge system getting perpetuated through folklore, local health traditions, tribal knowledge system, family and community based knowledge systems etc. All ancient cultures and civilizations of the world had thus evolved their own traditional food, nutrition and medicine from their ambient biological wealth. The Ayurvedic Masters of ancient India had a clear understanding of the delicate cellular mechanism of the body and the deterioration of the functional capacity of human being. To arrest such deterioration of the functional efficiency and to revive and revitalize the body system, the Ayurvedic masters developed an elaborate rejuvenation therapy known as ‘Rasayana’ therapy. ‘Rasa’ in Sanskrit means the essence and ‘ayana’ means to circulate in the body without any obstruction. ‘Rasayana’ is one of the eight clinical specialities of Ayurveda that is aimed for the rejuvenation and geriatric care. Rasayana is not a drug therapy, but a specialized procedure practiced to cleanse the body from the toxic and other microbial substances. In Rasayana Therapy, with the help of special diet and nutritional agents comprising of highly powerful antioxidants, the body is rejuvenated by providing greater immunity, vitality, longevity and by improving all faculties to attain youthfulness of the whole body.